Microbiological, physicochemical and labeling characterization of bottled coconut waters (Research, Society and Development, 2020)
Coconut water is a drink rich in electrolytes and can be used to help maintain body hydration. It has nutrient richness and high water activity, thus favoring the development of microorganisms, which in turn can alter the final quality of the product. Thus, the objective of the present research was to perform the microbiological, physicochemical and labeling characterization of bottled coconut waters. Thirty samples of bottled coconut water sold under refrigeration conditions in supermarkets were collected. Microbiological, physicochemical and nutritional labeling analyzes were performed. The presence of Salmonella spp. in 10% of the analyzed samples and high incidence of total coliforms. In addition, 80% of the samples were out of ideal cooling conditions, the same percentage in disagreement with the standards set by pH legislation and 100% of the irregular samples for titratable acidity. However, all samples were regular with respect to labels. Thus, the coconut waters marketed in the municipality of Mossoró / RN need greater hygiene-sanitary care and cooling conditions, in order to contribute to a safe drink for human consumption.